2018
DOI: 10.3390/colloids2020017
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic Behaviour of Mixed Films of an Unsaturated and a Saturated Polar Lipid. (Oleic Acid-Stearic Acid and POPC-DPPC)

Abstract: Mixed fatty acids or mixed phospholipids systems with saturated-unsaturated hydrocarbon chains are of biological interest. In this work, the monolayers of oleic acid-stearic acid (OA-SA) and palmitoyloleoylphosphatidylcholine-dipalmitoylphosphatidylcholine (POPC-DPPC) have been studied. From the surface pressure-area isotherms, elastic modulus values and virial equation coefficients can be obtained. Thermodynamic treatment also yields excess (G E ) and mixing (∆G mix ) free energies. Results indicate positive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 51 publications
1
3
0
Order By: Relevance
“…The value of b 0 is lower than 1, indicating that two-dimensional phospholipid aggregates may be formed under low surface pressure. The b 0 value of the POPC monolayer is higher than that of DPPC, and b 1 is positive, indicating that the main interaction between phospholipid molecules is repulsive [ 37 ], which is consistent with the result of A exc . The value of ( b 1 ) 12 ( X POPC = 0.4) is 0.2274 and is the lowest, significantly, while the corresponding value of A exc is close to 0 at a low surface pressure.…”
Section: Resultssupporting
confidence: 78%
“…The value of b 0 is lower than 1, indicating that two-dimensional phospholipid aggregates may be formed under low surface pressure. The b 0 value of the POPC monolayer is higher than that of DPPC, and b 1 is positive, indicating that the main interaction between phospholipid molecules is repulsive [ 37 ], which is consistent with the result of A exc . The value of ( b 1 ) 12 ( X POPC = 0.4) is 0.2274 and is the lowest, significantly, while the corresponding value of A exc is close to 0 at a low surface pressure.…”
Section: Resultssupporting
confidence: 78%
“…3 ), all while retaining the shape of the isotherm of pure Tween 60, the majority component. From a molecular point of view, DOTMA molecules feature two hydrophobic C18:1 oleic chains that make it surface active, in spite of having a net charge (a trimethylammonium group) in its polar headgroup [ 18 , 31 , 32 ], so it was expected to remain at the interface along with Tween 60 molecules, probably intercalating and interacting with them, as shown later.
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…This is consistent with the intercalation of unsaturated hydrocarbon chains, in this case in an amount proportional to DOTMA concentration, among saturated, single-chain stearic residues of Tween 60 molecules. The expanding effect of oleic chains has been reported in the literature for oleic acid/stearic acid [ 32 ] and saturated/unsaturated chain phospholipid interactions [ 33 ].…”
Section: Resultsmentioning
confidence: 99%
“…References to previous studies can be found in [1][2][3]. Some articles on single fatty acids and single phospholipids published in the last years are reported in reference [4]. Recent articles related to mixtures of fatty acid and a phospholipid are those of [5][6][7][8][9][10][11][12][13][14][15], and articles related to mixtures of cholesterol and a phospholipid are those of [16][17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%